Hydrodynamic studies in sectionalised external loop air lift reactors. Issue 1 (1st January 2021) - Teli, Shivanand M.; Mathpati, Channamallikarjun
ABSTRACT: External loop air lift reactor (EL-ALR) is widely used for multiphase reactions. They offer lower pressure drop and good heat and mass transfer rates compared to conventional bubble column reactors. In the case of fermentation applications where a medium is highly viscous and coalescing in nature, sectionalisation of riser helps in the improvement of the interfacial area as well as the reduction in liquid-phase backmixing. The present work deals with the measurement of the gas hold-up, mixing time, liquid dispersion, Sauter mean bubble diameter over a broad range of superficial gas velocities in sectionalised EL-ALR. Effects of electrolytes and surfactants have also been studied. Different plate designs have been studied for the sectionalisation. The correlations have been proposed for the gas hold-up, liquid circulation velocity, Sauter mean bubble diameter for superficial gas velocities. Abbreviations: EL-ALR: external loop air lift reactor; IL-ALR: internal loop air lift reactor; ADC: analog to digital converter; DAC: digital to analog converter.